COMUNICAÇÃO ORGANIZACIONAL INTEGRADA À IMPLANTAÇÃO DOS OBJETIVOS DE DESENVOLVIMENTO SUSTENTÁVEL: UMA PROPOSTA APLICADA À UFES. - Gonçalves, Jorgeana Antônio Azevedo (2021)
Faced with a globalized world, of economic and social contrasts, awareness of the collective becomes increasingly necessary. Advances in the economy is limited due to the exhaustible natural resources and sustainable development presents itself as a necessary alternative for organizations to face new challenges and consequently becomes stronger. Therefore, within the scope of the United Nations, the 2030 Agenda was developed and a set of Sustainable Development Objectives (SDOs) and goals, which will guide countries that participate for the next few years. Today, being a sustainable organization is a way to have a responsible role in the environment in which it operates, in addition to having positive image and gaining legitimacy. In this process, organizational communication becomes an essential tool for the relationship with different audiences, for transmitting information, but mainly for integrating, involving and mobilizing. The problem is that, although in vogue since 2015, Higher Education Institutions in Brazil are slowly implanting ODS. In 2020, Ufes started an institutional project to implement ODS and its structure, considering its key pillars of teaching, research and extension, aiming to create a regional, national and international sustainable development. Communication is extremely important for strategic planning and to align what will be done in order to effectively reach the entire academic community. The main objective of this dissertation was to analyze the strategic and institutional planning, to understand the reality and position of the institution in relation to Agenda 2030, to suggest a plan for viable and coherent action, which would inform and involve the academic community, since there is not a specific internal communication plan to implant SDOs at Ufes. One of the challenges is to create an awareness for the interlocutors by transforming information into knowledge and generate mobilization. In theoretical terms, the research was supported by theories about organizational communication, focusing on internal communication and its importance for public management. As for the methods and procedures, a qualitative approach, of an exploratory nature, was carried out by configuring the research as descriptive and functional. Data collection was carried out through a bibliographic survey and document analysis, partially structured interview and questionnaire. The result achieved was the current diagnosis by Ufes on the internal communication process and institutional planning aimed to achieve SDOs. Afterwards, an internal communication plan was developed as a technical product, using the vehicles provided by Ufes and seeking new alternatives of sharing media to broadcast in a systemic and integrated manner. Also, a collaborative map as part of communication strategies was proposed for spatial visualization of the actions related to the SDOs developed in the campus of Ufes, promoting the collaboration of the academic community, as well as to monitor the gradual evolution of such practices.